4D Printing of Electroactive Materials. (8th July 2021) - Chen, Andrew Y.; Pegg, Elizabeth; Chen, Ailin; Jin, Zeqing; Gu, Grace X.
Abstract : In recent years, the intersection of 3D printing and "smart" stimuli‐responsive materials has led to the development of 4D printing, an emerging field that is a subset of current additive manufacturing research. By integrating existing printing processes with novel materials, 4D printing enables the direct fabrication of sensors, controllable structures, and other functional devices. Compared to traditional manufacturing processes for smart materials, 4D printing permits a high degree of design freedom and flexibility in terms of printable geometry. An important branch of 4D printing concerns electroactive materials, which form the backbone of printable devices with practical applications throughout biology, engineering, and chemistry. Herein, the recent progress in the 4D printing of electroactive materials using several widely studied printing processes is reviewed. In particular, constituent materials and mechanisms for their preparation and printing are discussed, and functional electroactive devices fabricated using 4D printing are highlighted. Current challenges are also described and some of the many data‐driven opportunities for advancement in this promising field are presented. Abstract : A novel field in the current landscape of additive manufacturing research is the production of stimuli‐responsive four‐dimensional (4D) materials, termed "4D printing." Herein, recent progress in the 4D printing of electroactive materials is comprehensively reviewed. A variety of printable, electrically responsive materials and functional mechanisms are highlighted which enable a new generation of printable "smart" devices across multiple disciplines.